Constraints and preferences - Dziubalska-Kołaczyk, Katarzyna, 1960- (Trends in linguistics. Studies and monographs ;, 2011)
The central theme of this collection is the epistemological status of constraints and preferences in linguistics. The contributions focus mainly on phonology; one article deals explicitly with morphology. The approaches to phonology represented in the volume are those of Natural Phonology, Government Phonology, Optimality Theory, autosegemental phonology, and computational phonology. Constraints are juxtaposed either to rules or to preferences in the discussion of constraint-based vs. preference-based theories.